Designing reading tasks to foster critical thinking - Leda Maria Braga Tomitch (Ilha do Desterro)
What else is there besides multiple choice exercises, questions or true-false statements? What kind of readers do we EFL/ESL teachers, want to develop? Fortunately, there are alternative possibilities for designing reading activities which, besides being more interesting and fun for the students than the traditional tasks, can help develop more active and critical readers. A search in EFL/ESL reading textbooks has revealed that the most frequently encountered types of reading activities are comprehension questions, multiple-choice exercises, and true-false statements (Tomitch, in press a). These tasks have been used throughout the history of language teaching, and one must agree that they have their merits. However, there are reasons why they should not be used as the only source of activity in the classroom.